A novel approach to determine wet restitution coefficients through a unified correlation and energy analysis. Issue 3 (28th November 2014) - Sutkar, Vinayak S.; Deen, Niels G.; Padding, Johan T.; Kuipers, J.A.M.; Salikov, Vitalij; Crüger, Britta; Antonyuk, Sergiy; Heinrich, Stefan
<x xml:space="preserve">Abstract</x> Wet particle interactions are observed in many applications, for example, pharmaceutical, food, agricultural, polymerization, agglomeration, and coating, in which an accurate evaluation of the wet restitution coefficient (ewet) is crucial to understand the particle flowability, operating conditions and product size distribution. Experiments were performed to measure the wet restitution coefficient by impacting a spherical particle on a stationary plate covered with a thin liquid layer of water or glycerol solution in this work. Furthermore, novel approaches for estimation of ewet were developed using dimensional analysis (using the Buckingham π theorem and regression analysis) in combination with energy budget analysis. In the correlation development, the dominant physical properties of solid and liquid, particle impact velocity and liquid layer thickness are grouped into well‐known dimensionless numbers viz. Reynolds, Weber and Stokes. Whereas in the energy analysis, the energy dissipation rates were determined for five distinct collision phases, that is, dipping, dry collision, undipping, formation and breakage of the liquid bridge, and added mass. The efficacy of the developed approaches was analyzed by comparing obtained results with experiments and an elastohydrodynamic model, and a modified elastohydrodynamic model. © 2014 American Institute of Chemical Engineers AIChE J, 61: 769–779, 2015